2020
DOI: 10.3390/admsci10030046
|View full text |Cite
|
Sign up to set email alerts
|

Am I an Entrepreneur? Entrepreneurial Self-Identity as an Antecedent of Entrepreneurial Intention

Abstract: Although many studies have shown that entrepreneurial intention can be explained according to a theory of planned behavior, some scholars have provided interesting insights into the role of entrepreneurial self-identity perception as a significant precursor of entrepreneurial intention. A questionnaire was administered to graduates and students of an Italian university (N = 153). A hierarchical regression analysis controlling for demographic variables was performed in order to test the research hypotheses. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 88 publications
1
12
0
Order By: Relevance
“…These findings suggest that others' opinions and attitudes do not influence young returnees considering whether to engage in entrepreneurial activities. This conclusion is consistent with the finding of Ceresia and Mendola (2020). Some studies have shown that the three predictors of planned behavior theory have different effects on EI.…”
Section: Tpbsupporting
confidence: 92%
“…These findings suggest that others' opinions and attitudes do not influence young returnees considering whether to engage in entrepreneurial activities. This conclusion is consistent with the finding of Ceresia and Mendola (2020). Some studies have shown that the three predictors of planned behavior theory have different effects on EI.…”
Section: Tpbsupporting
confidence: 92%
“…The study of entrepreneurial intention stands out in the literature, being the intention generally considered by authors as the dependent variable in their studies of predictive and causal models. Intention is the variable that best predicts the behavior of creating a new company [52][53][54]. Entrepreneurial intention is defined as the state of mind that directs and guides a person's attention, experience, actions, goal setting and entrepreneurial behavior [9,51,53].…”
Section: Personal Variables Of Entrepreneurshipmentioning
confidence: 99%
“…Intention is the variable that best predicts the behavior of creating a new company [52][53][54]. Entrepreneurial intention is defined as the state of mind that directs and guides a person's attention, experience, actions, goal setting and entrepreneurial behavior [9,51,53].…”
Section: Personal Variables Of Entrepreneurshipmentioning
confidence: 99%
See 2 more Smart Citations